Actor and analyst: A response to Coopmans and Button. (October 2014) - Collins, Harry; Evans, Robert
We question the logic of Coopmans and Button's critique of our analysis of expertise on three grounds. First, their critique depends on a clear distinction between actor and analysts that we show cannot be maintained. Second, we question their reticence to allow the use of taxonomies in the analysis of expertise, suggesting that it is contradicted by their own descriptions of expert work, and we accuse them of making a mistake in the way they relate commonsense to specialist skills. Finally, we express our puzzlement at the antiseptic-like precautions that some ethnomethodologists apply to analysts' categories, especially given that – as we show – analysts' categories sometimes provide a superior resource for understanding and can change the actors' world as well as describing it.